An injectable shape-adaptive hydrogel system for subconjunctival injuries: In situ and permanently releases rapamycin to prevent fibrosis via promoting autophagy - Xue Sun; Haohao Cui; Jingfan Li; Boyuan An; Ruixing Liu; Zhihua Guo; Dandan Chu; Xingchen Geng; Bingbing Cui; Lei Zhu; Jingguo Li; Zhanrong Li (Materials Today Bio)
Subconjunctival fibrosis (SCF) is a common and refractory eye disease that is a serious threat to vision. The severe side effects of existing drugs and low drug bioavailability due to the ocular barrier are major challenges in SCF treatment. Hence, there is an urgent need to explore safer and more effective strategies for administering anti-SCF drugs. Herein, an injectable and adaptable hydrogel system containing the antifibrotic drug rapamycin was fabricated to address this complex need. This system possesses moderate mechanical properties, self-healing and shape-adaptive capabilities, injectability, and biosafety. It is designed to promote autophagy by modulating the PI3K/AKT/mTOR/WIPI2 pathway, thereby inhibiting SCF. In vivo experiments utilizing a rat subconjunctival injury model indicated that in situ administration of this hydrogel system effectively inhibited SCF. This system constitutes a promising method for promoting autophagy to protect against SCF, which will foster its widespread application for other fibrotic diseases.